Antioxidant and Cytotoxic Activitiy of Limonia acidissima L. (Dhaka University Journal of Pharmaceutical Sciences, 2012)
Not available DOI: http://dx.doi.org/10.3329/dujps.v11i1.12492 Dhaka Univ. J. Pharm. Sci. 11(1): 75-77, 2012 (June)